Prevalence of Musculoskeletal Pain among Iraqi Dentists - Alia Tabour Thijeel (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Prevalence of musculoskeletal disorders (MSD) very high among dentists world wide. Among these MSDs, neck pain & Low back pain are most common. Objective: After extensive search on prevalence of MSDs pain among dentists in different countries, we planned a study to examine prevalence among Iraqi dentists. Methodology: this study was cross sectional survey study conducted at Medical institute of Baghdad, Al-Falah dental center and Prosthetic and orthodontic dental center. Dentists were selected using simple randomized methods and using certain exclusion and inclusion criteria. Results: All participants filled the questionnaire forum . 44.4% were male, 66.6% female. Prevalence of back pain was 18.9% , Neck pain was 13.3%, 2.2% had hand pain, 30% had no pain. Conclusion: High prevalence of MSDs in general reach to about 70% and the most affected area were as fellow :Neck& shoulder , back and hand .Male and young age were more prone to different MSDs.